2017
DOI: 10.1136/jramc-2017-000809
|View full text |Cite
|
Sign up to set email alerts
|

A balance and proprioception intervention programme to enhance combat performance in military personnel

Abstract: The proprioceptive intervention programme for combat soldiers improved postural balance on unstable surfaces, and improved the correlation between postural balance in the eyes closed condition and postural balance following fatigue. Further longitudinal studies are needed to verify the relationship between proprioception programmes, additional weight bearing and the reduction of subsequent injuries in combat soldiers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Research has demonstrated that a proprioceptive intervention program enhanced the postural balance of combat soldiers when standing on unstable surfaces. Specifically, the soldiers’ ability to balance on a bosu ball significantly improved, particularly when doing so with their eyes closed [ 11 ]. The analysis of previous data reveals a connection between proprioceptive training and postural balance in both healthy adults and young athletes [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has demonstrated that a proprioceptive intervention program enhanced the postural balance of combat soldiers when standing on unstable surfaces. Specifically, the soldiers’ ability to balance on a bosu ball significantly improved, particularly when doing so with their eyes closed [ 11 ]. The analysis of previous data reveals a connection between proprioceptive training and postural balance in both healthy adults and young athletes [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over a period of four weeks, participants were involved in a training program comprising three sessions per week, with an average duration of 25 min for each session. Previous research conducted over a comparable time frame and duration (4 weeks, 10 min daily) has showed improved stability among military personnel [ 11 ]. Eleven training sessions were conducted on average.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dominant Leg. The dominant leg (the leg used when kicking a ball) for each subject was identified (10,42).…”
Section: Methodsmentioning
confidence: 99%